Penguatan Hafalan Al-Qur’an Siswa Melalui Metode Talaqqi - Annisatul wafa, Early; Abdurrohim; Mustofa, Taufik (Prodi Pendidikan Agama Islam (PAI) Fakultas Tarbiyah IAI Hamzanwadi NW Pancor, 2024)
Abstract This research aims to (1) To determine the process of strengthening students' memorization of the Qur'an through the talaqqi method in class VIII SMPIT Insan Harapan (2) To determine the supporting factors and inhibiting factors in the process of strengthening students' memorization of the Qur'an through the talaqqi method in class VIII SMPIT Insan Harapan. (3) To find out the results of strengthening students' memorization of the Koran through the talaqqi method in class VIII SMPIT Insan Harapan. This research uses a qualitative approach with descriptive qualitative methods. The type of data used in this research is qualitative data. Qualitative data is data that can only be measured indirectly. Data collection techniques were carried out using observation, interviews, documentation and tests. Data analysis techniques use data collection, data reduction, data presentation, and verification.The results of this research show that strengthening students' memorization of the Koran through the talaqqi method in class VIII SMPIT Insan Harapan shows better and smoother results. The process of strengthening students' memorization through the talaqqi method such as the teacher reading verses from the Koran and students repeating the reading until they are memorized, or students reading first and the teacher correcting the students' reading. The supporting factors are teacher commitment and patience, student consistency, family support, and a conducive learning environment. The inhibiting factors include limited time, lack of motivation, limited facilitation. The results of strengthening students' memorization of the Qur'an through the talaqqi method in class VIII SMPIT Insan Harapan shows that they can read the Qur'an fluently and in accordance with the laws of recitation and makharijul letters. Abstrak Penelitian ini bertujuan untuk (1) Untuk mengetahui proses penguatan hafalan al-qur’an siswa melalui metode talaqqi di kelas VIII SMPIT Insan Harapan (2) Untuk mengetahui faktor pendukung dan faktor penghambat proses penguatan hafalan al-qur’an siswa melalui metode talaqqi di kelas VIII SMPIT Insan Harapan. (3) Untuk mengetahui hasil penguatan hafalan al-qur’an siswa melalui metode talaqqi di kelas VIII SMPIT Insan Harapan.Penelitian ini menggunakan pendekatan kualitatif dengan metode kualitatif deskriptif dengan Jenis data yang digunakan oleh penelitian ini adalah data kualitatif. Data kualitatif yaitu data yang hanya dapat diukur secara tidak langsung. Teknik pengumpulan data yang dilakukan menggunakan observasi, wawancara, dokumentasi, dan tes. Teknik analisis data menggunakan pengumpulan data, reduksi data, penyajian data, dan Verification. Hasil penelitian ini menunjukkan bahwa penguatan hafalan al-qur’an siswa melalui metode talaqqi di kelas VIII SMPIT Insan harapan menunjukkan hasil yang lebih baik dan lancar. Proses penguatan hafalan siswa melalui metode talaqqi seperti guru membacakan ayat al-qur’an dan siswa mengulangi bacaan hingga hafal, atau siswa membaca terlebih dahulu dan guru mengoreksi bacaan siswa. Faktor pendukungnya yaitu komitmen dan kesabaran guru, konsistensi siswa, dukungan keluarga, lingkungan belajar yang kondusif. Faktor penghambatnya yaitu meliputi keterbatasan waktu, kurangnya motivasi, keterbatasan fasilitasi. Hasil dari penguatan hafalan al-qur’an siswa melalui metode talaqqi di kelas VIII SMPIT Insan Harapan menunjukkan bahwa mereka dapat membaca al-qur’an dengan lancar dan sesuai dengan hukum tajwid serta makharijul hurufnya.